Loading cargo onto cannery tender RED ROVER, Port Moller, ca. 1912 - Thwaites, John E. (John Edward), 1863-1940 (1912)
Caption on image: Red Rover, Loading Cargo PH Coll 247.925 Port Moller is a village in southwest Alaska. It is located on the Alaska Peninsula at the entrance of Port Moller Inlet (20 mi long) of Bristol Bay on the Bering Sea. Primary industries are fishing and fish canning. The motor cannery tender RED ROVER was built in 1913 for Pacific American Fishers